2010
DOI: 10.1111/j.1365-3083.2010.02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulin Free Light Chains in Severe Forms of Atopic Dermatitis

Abstract: An increase in immunoglobulin free light chains (FLC) was recently described in several pathological conditions, including asthma. FLC pathology is classically associated with monoclonal gammopathies. Its association with allergic disorders is surprising and unexplained. We therefore tested a cohort of children with severe atopic dermatitis (SCORAD 50–80) to determine the serum levels of free kappa and lambda chains, and correlated the results with clinical status and relevant laboratory markers. Seventy‐three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
2
20
1
1
Order By: Relevance
“…Therefore, another mechanism might be involved. Ig-fLC is a potential candidate, and plasma Ig-fLC concentrations were found to be increased in patients affected by cow's milk allergy and in infants suffering from AD as is the case in the current study (14,23). In a murine model for casein-induced food allergy, Ig-fLC was found to be pivotal for the acute allergic skin reaction and mast-cell degranulation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, another mechanism might be involved. Ig-fLC is a potential candidate, and plasma Ig-fLC concentrations were found to be increased in patients affected by cow's milk allergy and in infants suffering from AD as is the case in the current study (14,23). In a murine model for casein-induced food allergy, Ig-fLC was found to be pivotal for the acute allergic skin reaction and mast-cell degranulation.…”
Section: Discussionsupporting
confidence: 61%
“…Also Kayserova et al. (23) showed that both kappa and lambda Ig‐fLC were enhanced in serum from AD patients when compared to healthy age‐matched controls (n = 102). In the current study, the lambda Ig‐fLC concentrations correlated positively with total IgE.…”
Section: Discussionmentioning
confidence: 96%
“…We published earlier that serum levels of IgLC of patients with nonatopic asthma are increased (19). Also, in other chronic inflammatory conditions, such as rhinitis, dermatitis, and rheumatoid arthritis, increases in serum or local IgLC have been demonstrated (32)(33)(34) To our knowledge, we are the first to describe that IgLC may be associated with mast cell activation in the development of IBD. Our data in an experimental model for IBD support the presence of increased IgLC levels in serum and tissue from patients with IBD, whereas treatment with immunosuppressive drugs decreased serum IgLC.…”
Section: Discussionmentioning
confidence: 74%
“…возбу-дителям. Ведущая роль в развитии заболевания отво-дится иммунным нарушениям, наиболее значимыми из которых являются дисбаланс Th-1-и Th-2-клеток, повышенная дегрануляция тучных клеток и изменен-ная антигенпрезентирующая активность клеток Лан-герганса [19,28,34].…”
Section: атопический дерматит вульвы и/и ли проме жнос тиunclassified